Relationship between 25-hydroxyvitamin D Level and Metabolic Control and Albumin Excretion Rate in Elderly Patients with Type 2 Diabetes Mellitus - Fulden Sarac; Sumru Savas; Sefa Sarac; Fehmi Akcicek (Medicine Science, 2013)
The aims of the study were 1. to investigate the frequency of 25-hydroxyvitamin D deficiency and 2. to observe the relationships between D vitamin supplementation for 6 months and albumin excretion in elderly patients with type 2 diabetes mellitus. The study population included 100 patients with type 2 DM treated with insulin therapy (mean age 56.1±8.8 yrs) were enrolled in the study. Of 100 patients, 30 (mean age 65.4±6.4 yrs) had low 25(OH)D level. Patients with low 25(OH)D level received 50,000 unit of vitamin D3 orally per three weeks for 6 months. Albumin excretion rate (AER) was measured in patients with low level 25(OH) D before and after D vitamin supplementation In study group (n= 100), 30 patients had low 25(OH)D level. Concentrations of 25(OH)D were; 10 (33.3%) had insufficient vitamin D levels, 19 (63.4%) had deficient levels, 1 (3.3%) had severe deficiency in patients with deficiency. There were statistically significantly differences for plasma levels of HbA1c (p=0.001), postprandial glucose (p=0.0001), triglyceride (p=0.04), total-Cholesterol (p=0.03), LDL-Cholesterol (p=0.02), and HDL-Cholesterol (p=0.001) between D vitamin supplementation. There were high frequency of 25(OH)D deficiency in patients with type 2 diabetic patients. And also, D vitamin suplementation changed metabolic parameters such as triglyceride, total-Cholesterol, LDL-Cholesterol and HDL-Cholesterol, postprandial glucose and HbA1c levels but not albumin excretion rate. [Med-Science 2013; 2(4.000): 852-62]